Photoplethysmography in dogs and cats: a selection of alternative measurement sites for a pet monitor - Cugmas, Blaž; Štruc, Eva; Spīgulis, Jānis (IOP Publishing, 2019)
Objective: Photoplethysmography (PPG) is an increasingly popular health and well-being tool for monitoring heart rate and oxygen saturation. Due to the pigmentation and hairiness of dogs and cats, a pulse oximeter is routinely placed solely on the tongue. As this approach is feasible only for pet monitor use during surgical procedures, we investigate PPG signal quality on several other measurement sites that would be better tolerated by conscious animals. Approach: Acquired PPG signals are analyzed by four signal quality indices: mean baseline, signal power, kurtosis, and tolerance score. Main results: In dogs, the metacarpus and tail can be substituted for oral pulse oximeter placement since both measurement sites exhibited high PPG signal kurtosis and were considered well-tolerated. In cats, the digit could be used with some limitations. Significance: Pet monitors with pulse oximeter probes adjusted to promising measurement sites could enable veterinarians and owners to monitor animals when fully awake.
Keywords: photoplethysmography; pulse oximeter; oxygen saturation; motion artefact; heart rate; pet monitor; Research Subject Categories::NATURAL SCIENCES::Physics::Atomic and molecular physics